Complementary mesoscale dynamics of spectrin and acto-myosin shape membrane territories during mechanoresponse - Andrea Ghisleni (Nature Portfolio, 2020)
The cell cortex that supports the plasma membrane contains spectrin, a protein that interacts with the acto-myosin cytoskeleton. Here, the authors analyze spectrin behavior during cellular mechanoresponse and membrane trafficking, and observe spectrin regulation by myosin-driven contractility.